A Combinatorial Interpretation of the Padovan Generalized Polynomial Sequence - Passos Machado Vieira, Renata; Vieira Alves, Francisco Regis; Machado Cruz Catarino, Paula Maria (Armenian Journal of Mathematics, 2023)
We investigate a combinatorial interpretation of the Padovan polynomial sequence, also addressing its polynomial extensions. We thus include the Tridovan polynomial sequence, Tetradovan polynomial sequences, leading up to the Z-dovan polynomial generalization.
Keywords: Combinatorics; Generalization; Padovan Polynomial Sequence